Design Of Agricultural Motivation Media And Agricultural Industry In The Covid-19 Pandemic Period - I Nyoman Anom Fajaraditya Setiawan; I Nyoman Widhi Adnyana; Putu Wirayudi Aditama (ADI Journal on Recent Innovation, 2021)
The agricultural sector is not only for the discourse of food sovereignty, but one of the foundations of the economic strategy. The erosion of agriculture by the opportunities of other sectors, refers to the focus of research in Bali's Celuk Buruan Village, by uncovering phenomena that occur in this region. The existence of regional development, the availability of access and public facilities, is a problem in the agricultural sector in this region. Changes in perspective or land-use change are inevitable, impacting agriculture and small businesses that have long worked with farmers to drive the village economy. Based on the phenomenon, an idea arose to revive the agricultural and industrial sectors in Celuk Buruan. During the Covid-19 pandemic crisis, the decline of Bali's tourism, with a qualitative approach, attempted to design, which could provide positive input to the situation. The design of media about agriculture is a preventive action, carried out in a structured, processed in the design of visual communication. In the end, communication media can produce to answer the problem and widely disseminated on the internet media.